let f(x)=3x-3 and g(x)=2/x-1. evaluate:
a)2fg(2)
b){f/g-2f)(3)
c)(f-g)(4)
3 answers
a. 2(3(2)-3) =6 b.(-6x^2+8)/(x-1) c.(12x^2-24x+4)/(x_1)
You have some matching problems with braces and parens, but
2(fg)(2) = 2*f(2)*g(2) = 2*3*2 = 12
(f/g-2f)(3) = f(3)/g(3) - 2f(3) = 6/1 - 2*6 = -6
(f-g)(4) = f(4)-g(4) = 9-2/3 = 8 1/3
kobe needs to step back and take a breath.
2(fg)(2) = 2*f(2)*g(2) = 2*3*2 = 12
(f/g-2f)(3) = f(3)/g(3) - 2f(3) = 6/1 - 2*6 = -6
(f-g)(4) = f(4)-g(4) = 9-2/3 = 8 1/3
kobe needs to step back and take a breath.
Answer